Portuguese agriculture and its role in multifunctional rural development - Ventura-Lucas, Maria Raquel; Marques, Carlos; de Belém Martins, Maria; Fragoso, Rui (Applied Studies in Agribusiness and Commerce, 2010)
AsinEurope,agricultureinPortugalissupposedtofulfill a multiplicity of roles. It should contribute to supply Portuguese population with quality and safe food, to be viable in a global, competitive, dynamic and aggressive market, to preserve precious cultural landscapes across country through sustainable land management, to assist rural areastobeattractiveandfeasibleandtosupportemployment and social cohesion. Nevertheless, adjustments are expected to adapt to new environmental conditions, mainly climate change, to minimize weaknesses, to hold new opportunities and face new challenges. Otherwise, increases on human desertification, rural areas abandonment and consequent negative effects on territory are predictable.